Inovasi Penilaian Autentik Berbasis Padlet dalam Pembelajaran Sharaf - Azmalia Anastasya Marcella; Zamakhsari Zamakhsari (Lembaga Yasin AlSys, 2026)
Authentic assessment in Sharaf learning needs to be developed innovatively so that it can assess not only final outcomes but also students’ thinking processes, word-form analysis, and learning experiences in a more meaningful way. This study aims to describe innovations in authentic assessment based on digital media in Sharaf learning. This study used a qualitative approach with a library research design, or library research, focusing on a conceptual review of various scientific literature sources without directly involving field studies. The research data consisted of secondary data obtained from journals, books, proceedings, and academic documents relevant to authentic assessment, Sharaf learning, and the use of digital media in education. Data were collected through documentation study by tracing, identifying, and classifying literature according to the research focus, then analyzed using content analysis techniques, or content analysis, through the stages of data reduction, data display, and interpretative conclusion drawing. The results of the study show that the use of digital media such as Padlet has the potential to support the implementation of authentic assessment in Sharaf learning because it enables students to present the process of word-form analysis openly, interactively, and in a documented manner. This medium also facilitates interaction among students and provides space for teachers to understand students’ thinking processes more comprehensively. The conclusion of this study affirms that digital media-based authentic assessment can serve as an innovative alternative in developing evaluation practices that are more contextual, participatory, and meaningful in Sharaf learning. The implications of this study provide conceptual contributions to the development of digital-based Arabic language assessment and serve as a reference for teachers in designing assessments oriented toward students’ processes, participation, and understanding.